Respiratory physiologist training in Ireland. Issue 3 (September 2017) - Flood, Emma
Respiratory physiologists are part of a large multidisciplinary team. Their role is to investigate respiratory and sleep disorders through various diagnostic tools and methodologies. In Ireland, respiratory physiologists complete a 4-year Bachelor of Science (BSc) degree in clinical measurement science.